Application of Employee Competencies In The Use of GIS Website Digitalization - Amaliyah, Amaliyah; Sinulingga, Rizky Amalia; Dimisqiyani, Erindah; Apsari, Citra Widhi (AIBPM Publisher, 2024)
The rapid advancement of technology has become integral to all aspects of modern life. This research examines the relationship between employee competency and the use of a digitalized GIS website for managing customer data, focusing on employees at PDAM Surabaya City. The study involved 100 participants and employed a quantitative descriptive approach, utilizing data collection techniques such as observation, interviews, and surveys through questionnaires. Findings reveal that while employees generally believe their education and technological skills are well-suited to their job roles and support their performance, there are notable issues with the GIS website's reliability and error management. The high consensus on the need for improvements highlights the importance of ongoing maintenance and user support. Statistical analysis confirms that employee competencies significantly impact the effective use of the GIS website, underscoring the importance of skill development in optimizing digital tool utilization and enhancing organizational efficiency. The research implies that improving employee competencies and addressing technical issues with the GIS website are essential for enhancing its utilization and overall organizational performance.